Popular Cinema as Political Theory - Nelson, J. author. aut Link
XII, 249 p.
Keywords: The book presents cinematic case studies in political realism versus political idealism, demonstrating methods of viewing popular cinema as political theory. The book appreciates political myth-making in popular genres as especially practical and accessible theorizing about politics.